Special Circumstances for Sentencing for Criminal Offenses Against the Environment - Mrvić, Milena; Hubić Nurković, Lejla (Glasnik Advokatske komore Vojvodine, 2026)
Absolutely — here it is with American English spelling: Environmental criminal offenses, as a separate group of criminal offenses, are prescribed in Chapter XXIV of the Criminal Code of the Republic of Serbia and constitute a specific group of incriminations reflecting contemporary challenges in the preservation of natural resources and human health, since they disturb ecological balance, endanger human health, and cause lasting consequences for natural resources. Their distinctive nature lies in the fact that their consequences are most often not limited to an individual or to the moment of commission, but extend to the wider community, the public interest, and future generations. Sentencing for these criminal offenses should entail a different approach compared with classical criminal offenses, namely, in this type of criminal offense, particular consideration should be given, when determining the sentence, to the scope and gravity of the actual or potential damage to the environment, the duration and irreparability of the consequences, the degree to which human health has been endangered, the motive and benefit obtained by the offender, and especially the conduct of the accused after the commission of the criminal offense, including remediation, compensation for damage, and cooperation with the competent authorities. The paper examines the normative frameworks of the Republic of Serbia and the European Union, analyzes the specific circumstances arising in the process of sentencing, provides an overview of the prosecutorial and judicial practice of domestic courts, as well as the standards developed in the judgments of the European Court of Human Rights. Particular attention is devoted to the efforts of the Republic of Serbia to harmonize its legislation and practice with European standards in the field of environmental protection. The aim of the paper is to demonstrate the specific features of environmental criminal offenses, which require a differentiated, stricter, and remedial approach to sentencing, one that should be proportionate, dissuasive, and directed toward the prevention of future violations, in order to ensure effective protection of the environment and achieve the objectives of general and special prevention.